Legal Economic Literation of Digital Marketing for PKK Groups as an Independent Economic Development Efforts for Communities Affected by Covid-19 - Takarini, Nurjanti; Wahyudi, Eko; Mahanani, Anajeng Esri Edhi (Nusantara Science and Technology Proceedings, 2020)
The impact of covid-19 is not sufficiently impacting the health sector, the economic sector is equally affected. The existence of large-social restrictions, policies that scale psychological distancing cause the economic condition of the community to chaos. The scope of society that is then most affected is the people with the middle to lower economy. Surabaya, which is one of the industrial trading cities, is economically affected. The effect of the rapidly declining trading business conditions was influenced by the conditions of trading business in Indonesia and even the world. The world economy is currently on the worst curve. An increase in unemployment also occurred in the city of Surabaya. Several business businesses in Surabaya have closed down due to the impact of the Covid-19 pandemic. It is necessary then to think about efforts to get out of the big hole of the economic downturn. The community must be independent to build the family economy. This should be the focus of the economic development of the family. Increasing home-based trading is an effort that can be initiated by each family, to build an independent economy, without depending on a country that is currently also at a low economic point. Through the economic independence of the family, the hope is that it will build the country's economy slowly but surely. This dedication moves the PKK organization to encourage home-based business by utilizing information technology media. Apart from that, it also encourages people to be literate in law and economic legal policies to support the economic independence that will be built.